2020
DOI: 10.21278/tof.43402
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Factorial Experiment with Repeated Measurements in the Investigation of Parameters Influencing the Properties of Niobium Microalloyed Cold Drawn Welded Steel Tubes

Abstract: It has been observed that inhomogeneous deformations occur at the beginning of the plastic material flow during the cold drawing of welded tubes and after the proportionality limit R p has been reached. Therefore, it is important to determine the most influential factor at the beginning of the plastic material flow. Tests were carried out on a welded joint and on the base material. The study was performed on two steels with different contents of the microalloying element niobium. Tubes were drawn with two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The tendency of Sadowski et al [20] to model the phenomenon of Lüders bands by regression analysis is manifested where they sought to model different yield plateau gradients for different structural carbon steels. Rešković et al [21] used factorial experiment with repeated measurements to determine influence of different factors at the proportionality limit after which Lüders bands appear in niobium microalloyed steel during cold deformation. They concluded that the deformation degree has the greatest influence on the proportionality limit during cold drawing of niobium microalloyed steel tubes.…”
Section: Introductionmentioning
confidence: 99%
“…The tendency of Sadowski et al [20] to model the phenomenon of Lüders bands by regression analysis is manifested where they sought to model different yield plateau gradients for different structural carbon steels. Rešković et al [21] used factorial experiment with repeated measurements to determine influence of different factors at the proportionality limit after which Lüders bands appear in niobium microalloyed steel during cold deformation. They concluded that the deformation degree has the greatest influence on the proportionality limit during cold drawing of niobium microalloyed steel tubes.…”
Section: Introductionmentioning
confidence: 99%